Detection of delamination onset in laser-cut carbon fiber transverse crack tension specimens using acoustic emission. (September 2015) - Prieß, Torben; Sause, Markus GR; Fischer, Daniel; Middendorf, Peter
Numerous experimental studies have been made on cutting carbon fibers with lasers with the focus on productivity due to high cutting speeds. However, the laser-cutting process has an influence on the mechanical properties of the carbon fiber-reinforced plastic. This paper presents a test to determine the impact of thermal damage at the cutting edge. The initiation load for mode II delamination at the transverse crack tension test can be used to estimate the impact on the mechanical properties of thermal damage at the cutting edge. Detection of the initiation load is done via acoustic emission methods. Two different specimen geometries show a decrease of more than 40% of the initiation load for a CO2 continuous wave laser system with a large heat-affected zone compared to mechanically cut specimens.